Awareness of menstrual cup among reproductive age group women - Bharatnur, Sunanda; Aishwarya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: The first type of menstrual cup having a bullet-shape was patented in 1932 by the midwifery group of McGlasson and Perkins. The first medical grade silicone menstrual cup was manufactured in 2001 by Mooncup UK. Menstrual cups are considered as environmentally friendly and inexpensive alternative to expensive disposable pads. The capability to reuse the cups with a service life of 10 years is a significant advantage of menstrual cups. Menstrual cups have been in use since a long time but very limited studies are conducted about their awareness among Indian women. Hence, in this present study, the awareness of menstrual cup among reproductive age group women was evaluated. Methods: Data was collected from the eligible and chosen women in reproductive age through a pre-developed questionnaire and completed in the presence of the interviewer. It was a descriptive cross-sectional study conducted over a period of 1 month in Srinivas Institute of Medical Sciences and Research Centre, Mangalore, Karnataka, India. Results: In this study, total of 508 participants were included. The maximum number of participants was in the age group of 21 years to 25 years (58.46%). The educational status of the participants was mostly in the category of undergraduate level (69.88%). The marital status of most of the participants was unmarried (89.37%). Most of the participants belong to low-income group (<Rs.20000-72.44%). 465 participants (91.5%) have heard about menstrual cups but only 1.57% of them were using menstrual cups alone whereas around 9.8% use them occasionally along with other methods. Conclusions: Menstrual sanitary management is difficult in low-income reproductive aged women due to conventional way of life, lack of knowledge on best sanitary practices, and restricted access to suitable and reasonably priced menstrual hygiene products. As an alternative to sanitary napkins, menstrual cups can be effectively used to contain the menstrual flow. Even though it is observed that the awareness about menstrual cups is very good among the reproductive aged women in India, the usage is very limited. As menstrual sanitary management is a more and more important issue and as India is facing a major threat in the form of managing the soiled napkins waste which results in multiple complications, the usage of menstrual cups must be promoted.